The phantom carriage [videorecording (DVD)] - Sjöström, Victor, 1879-1960; Borgström, Hilda, 1871-1953; Svennberg, Tore, 1858-1941; Holm, Astrid, 1893-1961 (Criterion collection, 2011)
As the clock approaches midnight on New Year's Eve, an abusive alcoholic looks for redemption or he is doomed to take the reins of Death's carriage for the entire next year, gathering the souls of sinners.